Ethics and hidden greed : your defense against unethical strategies and violations of trust - Docters, Rob; Gieskes, Hans (Emerald Publishing Limited, 2023)
Trust. Loyalty. Friendship. These were once the building blocks of good business relationships. Today, it's becoming increasingly difficult to know whom to trust. How do we protect ourselves and our business interests from the unethical behaviours of others? Why doesn't intuition serve as the best guide for detecting unethical strategies? Concern about falling victim to the tactics of unethical strategies is widespread. The authors connect time-honoured ethical principles to real-world cases and offer the building blocks and counter-strategies you need to fight greed: Knowing the five strategies of greed, and learning how to recognize them. Learning how trust really works, and being able to develop the skill of trusting with discernment. Applying, and being able to communicate, concrete, ethical rules. Ethics and Hidden Greed will reassure readers that while unethical strategies may have increased in sophistication and grown harder to detect in recent years, there are still only five categories of these behaviours. The authors will demonstrate how to recognize the patterns employed by greedy players and provide tactics for combatting all of them.